Erratum: BAÑON, R., VILLEGAS-RÍOS, D., SERRANO, A., MUCIENTES, G. & ARRONTE, J.C. (2010) Marine fishes from Galicia (NW Spain): an updated checklist. Zootaxa, 2667, 1–27. - Bañon, R.; Villegas-Ríos, D.; Serrano, A.; Mucientes, G.; Arronte, J. C. (Zootaxa, 2010)
(Erratum)